Animais como pessoas: a abordagem abolicionista de Gary L. Francione - Trindade, Gabriel Garmendia da (2013)
The present study addresses the Abolitionist Approach to Animal Rights proposed by the American legal scholar Gary L. Francione. This research aims to discuss three h v w h h : h moral relationship between humans and nonhumans; (B) the property status of nonhuman animals; (C) the philosophical grounding for a moral theory in defense of nonhuman animals based solely on sentience. For doing so, this study not only x h k g q y h h h perspectives of other authors. In view of this, the present dissertation is divided in three chapters. In the first chapter, it will be investigated the issue of the moral relations held between human beings and nonhumans animals. Major emphasis will be placed on the analysis of the d moral schizophrenia the last one was coined by Francione. In the second chapter, it will be detailed the moral and legal status of nonhuman animals as economic resources and its numerous theoretical and practical implications. Other key issues approached in this h h y K h hy defense of animal rights, and a reconstruction of the debate among Francione and Robert Garner on the relation between equal consideration of interests and property. In the third chapter, four major themes will be subject of problematization: (a) the attempts to exclude nonhuman animals from the moral community; (b) the similar-minds theory of the human/nonhuman relationship; (c) the lifeboat dilemma, the harm of death on sentient beings and their interest in continued existence; and (d) the creation of an animal rights moral theory based solely on sentience and the extension of the moral personhood to all sentient nonhuman animals. As a general conclusion, it will be sustained that the extension of moral personhood as well as moral rights to nonhuman animals will lead to the abolition of institutionalized animal exploitation.